Effect of TIG welding parameters in joining grade 2 pure titanium - Sonmez, Murat; Topuz, Polat (WALTER DE GRUYTER GMBH, 2021)
Grade 2, the most widely used pure titanium in the industry, has high corrosion resistance, excellent ductility, good weldability and is easily machinable. If titanium is exposed to temperatures above 500 degrees C due to moisture or hydrocarbons in the air, it is susceptible to taking up oxygen, nitrogen, carbon and hydrogen. This can cause cracks, especially after welding. Therefore, protection of the welding zone from external factors is of great importance during welding. For these reasons, TIG welding is the most widely used method for titanium welding. In this study, Grade 2 pure titanium plates are joined by TIG welding at three (40 A, 60 A and 80 A) current values under the same conditions. For the welding process, 2 wt.-% cerium addition Tungsten tip and high purity (99.99 vol.-%) argon was used as a shielding gas. After a visual inspection of the welded samples, microstructure inspections, macrostructure inspections, hardness measurements, bending tests and tensile tests were performed in accordance with the standards. As a result of the investigations, it was determined that the most suitable current value for the joining of Grade 2 titanium by TIG welding was 60 A.
Keywords: Grade 2 pure titanium; weldability; TIG welding; welding current; shielding gas; Materials Science